Implementasi Nilai-nilai Social Emotional Learning (SEL) melalui Permainan Monopoli Sistem Pendengaran Untuk Siswa SD (Universitas Negeri Semarang, 2019)
This study aims to develop a media evaluation based on monopoly games to learn the values of Â Social Emotional Learning (SEL) for Grade IV Elementary School students on hearing system material. This type of research is a Research and Development (RnD) with ADDIE design (Analysis, Design, Develop, Implement, and Evaluate). The stages carried out for this research are limited to the Development stage. The results of this study are in the form of a monopoly evaluation media, hereinafter referred to as Hearsmon, which contains test instruments related to the hearing system material for grade IV students. The values of Social Emotional Learning (SEL) developed through this media include personal dimensions (self-awareness, self-efficacy, self-management) and social dimensions (respect for others).Â Keywords: Social Emotional Learning, implementation, monopoly games, hearing systems, elementary school students.